Produção de gesso de revestimento interno utilizando anidrita II - Albuquerque, Cristina Maria Alves Morais de (2016)
The plaster projection was developed as a cast material over, to be incorporated into construction systems used in construction.Your application must include interior of the houses and buildings, both commercial and residential, shops, malls,hospitals,etc.These grounds requires is a perfect technique for use in order to have quality and performance to ensure the standards required by the current market, mainly to reduce the consumption of natural resources, ensuring the least possible amount of waste produced during and after the application process. The literature has given very little.scientific information on the production of this type of plaster, due to the essentially commercial nature of this area.In practice it is known that in Plaster Pole of Araripe-Pernambuco, this type of plaster has been made improperly, with inadequate dehydration of the mineral gypsum ore (on conversionreaction), being completed with the incorporation of additives - limited substances, such as the glue plaster; that the high cost adds value.This work, therefore, the objective is to show how the development of a basic projection process of gypsum production, with the aid of totally dehydrated gypsum (anhydrite II). Consisted of hemihydrates and anhydrite II in suitable percentage for fixing setting time required for a better workability.of the mass. This type of plaster has advantages in relation to those produced by current procedures practiced in the Plasterer Polo Araripe, associated with a significant reduction of waste - basic concern that one should have in relation to the duration of deposits.